2012
DOI: 10.2166/ws.2012.131
|View full text |Cite
|
Sign up to set email alerts
|

No simple solution to waterborne fungi: various responses to water disinfection methods

Abstract: Control strategies against waterborne fungi have been studied only to a small degree. In order to increase knowledge of the effect of water treatment on waterborne fungi, the dose–response effect of four commonly used drinking water disinfection methods was tested on selected fungal species: Aspergillus calidoustus, Penicillium spinulosum, Trichoderma viride and Fusarium solani. These species are all common in Norwegian drinking water, and are regarded as emerging pathogens, toxigenic and/or food contaminants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 0 publications
1
14
0
3
Order By: Relevance
“…Drinking water companies in the Netherlands do not apply chlorination in their treatment process, neither for primary disinfection nor to maintain residual disinfectant in the distribution network. Although the susceptibility of pathogenic fungal species to disinfection has not been explored as much as it has been done for protozoa, bacteria and viruses, some studies in drinking water demonstrated that certain fungal species were resistant to commonly applied levels of chlorination (Hageskal et al, 2012;. Swimming pools apply a higher concentration of residual free chlorine (0.5-1.5 mg/L (Bhvbz, 2011)) compared to drinking water (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Drinking water companies in the Netherlands do not apply chlorination in their treatment process, neither for primary disinfection nor to maintain residual disinfectant in the distribution network. Although the susceptibility of pathogenic fungal species to disinfection has not been explored as much as it has been done for protozoa, bacteria and viruses, some studies in drinking water demonstrated that certain fungal species were resistant to commonly applied levels of chlorination (Hageskal et al, 2012;. Swimming pools apply a higher concentration of residual free chlorine (0.5-1.5 mg/L (Bhvbz, 2011)) compared to drinking water (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A number of utilities in countries such as Norway (∼25%), Germany (∼50%) and the Netherlands (approaching 100%) do not use a disinfection residual during distribution but some do use UV radiation at the treatment stage. 19,134 Hageskal et al 130 demonstrated that the most common fungi in Norwegian DWDS 135 are those with an ability to survive the UV disinfection (potentially due to their pigmentation), primarily Penicillium spinulosum, and Trichoderma viride. The Netherlands and Switzerland, also aim towards producing high-quality drinking water via implementation of alternative methods to chemical disinfection 11 such as ultra-filtration or reverse osmosis, 136 which primarily control growth-limiting substrates.…”
Section: Disinfectionmentioning
confidence: 99%
“…al., 1996) Whitehouse et al, (1991) amostras de 11 tubulações, Williams et al, (1993) que coletaram de 150 equipos, Barbeau et. al., (1996) 1985;FANTINATO et al, 1992;AGUIAR;PINHEIRO, 1999;APHA, 1999;NOCE;PUTNINS, 2000;SOUZA-GUGELMIN et al, 2003, PETTI;TARSITANI 2006;SACCHETTI, 2009;HAGESKAL et al, 2012;DALLOLIO et al, 2014), apresentou menor recuperação de UFC/mL, quando comparados com os meios R2A ou PD, fato que também foi constatado por Reasoner e Geldreich em O meio de cultura R2A e PD foram desenvolvidos especialmente para a contagem de bactérias totais da água (REASONER;GELDREICH, 1985;MAKI et al, 1986;BARBEAU;BUHLER, 2001;UZEL;COGULU;ONCAG, 2008;BOYLE et al, 2010;ZHANG;SILEIKA;PACKMAN, 2012;ÖZALP et al, 2013 A maioria dos trabalhos somente avaliou a presença dos micro-organismos na água (REASONER;GELDREICH, 1985;PUTTAIAH et al, 1998;LIN et al, 2011;KRAMER et al, 2012;ÖZALP et al, 2013) e quando analisou qualitativamente, os meios de cultura não foram específicos para água ou específicos para certas espécies bacterianas ou fúngicas e, o emprego de meios diferentes do PCA, R2A e PD (MAKI et al, 1986;WHITEHOUSE et al, 1991;GONÇALVES;…”
Section: Discussionunclassified
“…Penicillium sp teve prevalência de 21,84%, e não foi isolado somente na clínica de pós-graduação, mas foi detectado independente dos meios de cultura, local de coleta ou técnicas de isolamento (ARVANITIDOU et al, 1999;GONÇALVES;PATERSON;LIMA, 2006;SZYMAŃSKA, 2006;HAGESKAL et al, 2012;SIQUEIRA;LIMA, 2013 1977;ARVANITIDOU et al, 1999;KELLEY et al, 2003;GONÇALVES;PATERSON;LIMA, 2006;SZYMAŃSKA, 2006;SAMMON et al, 2010;HEDAYATI et al, 2011; BERMEJO, 2012; AL-GABR; ZHENG; YU, 2013; SIQUEIRA; LIMA, 2013).…”
Section: Discussionunclassified
See 1 more Smart Citation